Laparoscopic liver resection for treating recurrent hepatocellular carcinoma. Issue 5 (June 2013) - Kanazawa, Akishige; Tsukamoto, Tadashi; Shimizu, Sadatoshi; Kodai, Shintaro; Yamamoto, Satoshi; Yamazoe, Sadaaki; Ohira, Go; Nakajima, Takayoshi
Abstract Background It is still unknown whether laparoscopic liver resection is suitable for recurrent hepatocellular carcinoma (HCC) after previous curative hepatic resection. Method The perioperative outcomes of 40 patients treated with second surgery for recurrent HCC by partial hepatectomy were studied retrospectively. The second surgery was performed under laparotomy in 20 patients (laparotomy group) and under laparoscopy in 20 patients (laparoscopy group). Results Intraoperative blood loss (p < 0.0001) and the incidence of postoperative complications (p = 0.0004) were lower in the laparoscopy group than in the laparotomy group. The incidence rates of surgical site infection and intractable ascites were significantly higher in the laparotomy group than in the laparoscopy group (p = 0.0202, p = 0.0436, respectively). The proportion of patients classified as Clavien grade IIIa was higher in the laparotomy group than in the laparoscopy group (p = 0.0033). The duration of the postoperative hospital stay was significantly shorter in the laparoscopy group than in the laparotomy group (p < 0.0001). Conclusions Postoperative morbidity has been decreased by the introduction of laparoscopic liver resection in patients with recurrent HCC after curative hepatic resection. As a result, the duration of the postoperative stay is shorter.